Racial differences in dementia‐related pathology underlying cognitive decline: The Multi‐Ethnic Study of Atherosclerosis (MESA). (1st February 2022) - Hughes, Tim M.; Schaich, Christopher L.; Lockhart, Samuel N.; Hiatt, Kevin; Whitlow, Christopher T.; Jung, Youngkyoo; Bertoni, Alain; Burke, Gregory L.; Solingapuram Sai, Kiran K.; Heckbert, Susan; Craft, Suzanne; Rapp, Stephen R.; et al.
Abstract: Background: Racial differences in dementia‐related pathology are purported to underlie health disparities in Alzheimer's disease and related disorders. We examined the prevalence and relevance of neuroimaging biomarkers of cerebral small vessel disease (cSVD), and β‐amyloid (Aβ) deposition in cognitive decline and impairment among a diverse cohort of older adults. Method: Participants at the Wake Forest MESA site were recruited at Exam 6 (2016‐19) to receive additional detailed cognitive testing, cognitive adjudication, and multimodal neuroimaging. Brain MRI on 3T Siemens Skyra, included T1, SWI, FLAIR and NODDI sequences. Total gray matter and white matter hyperintensities (WMH) volumes were adjusted for intracranial volume. A single neuroradiologist graded vascular lesions, including cerebral microbleeds, large and lacunar infarcts. Cognitive decline was measured by the Cognitive Abilities Screening Instrument (CASI) at Exam 5 (2010‐12) and Exam 6 (2016‐19). A subset of 157 participants completed Aβ‐PET at Exam 6 to quantify Aβ burden and positivity (PiB SUVR ≥1.21). Multivariable linear and logistic regression modeled neuroimaging parameters with change in CASI and cognitive status adjusted for age, gender, education, and APOE genotype, considering potential interactions by race. Result: The imaging sample included 252 participants (53% African‐American and 47% White; aged 72±7 years; 58% women, Table 1). 27% of participants were adjudicated to have mild cognitive impairment (MCI) and 4% had dementia. Aβ positivity (36%) and cSVD (microbleeds in 37% and lacunes in 32%) were common and did not differ by race. Further, temporal lobe cortical thickness and WMH volumes did not differ by race. Lower total gray matter volume, higher WMH volumes, and lower temporal lobe cortical thickness were consistently associated with greater cognitive decline and impairment across racial groups (Table 2). Significant interactions between race and imaging biomarkers with cognitive decline and impairment observed for: greater NODDI Free Water only in White participants and microbleeds and Aβ only in African‐American participants. Conclusion: Imaging biomarkers indicative of cSVD and Aβ are common in older adults. These biomarkers were not more prevalent in African‐American than White older adults as previously reported; however, they appear to be more strongly related to cognitive decline and impairment among African‐Americans.